2013
DOI: 10.1521/soco.2013.31.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Back to Basics: Socially Facilitated Situated Cognition

Abstract: A widely ignored finding in social facilitation suggests that the mere presence of others increases the "spreading out" of one's thoughts (Allport, 1920). Here, we revisit this finding and expand upon it using a situated cognition perspective.Experiment 1 approached the spreading-out-of-thought effect using the same free-association task as Allport. Results replicated and extended previous findings. Compared to an alone condition, co-action and mere presence activated more associations, being that these associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…As such, it is possible that the presence of others, instead of engaging individuals in a task, makes them more sensitive to the context. In line with this hypothesis, Fonseca and Garcia-Marques (2010) have demonstrated that, compared to an alone situation, the presence of others increases the amount of contextrelated free-associations (experiment 1) and the accuracy for estimation judgments that require the integration of contextual information (experiment 3). This context-sensitivity hypothesis can also be found in social facilitation evidence that shows that accompanied individuals have better recall for contextual aspects of the task-situation, (Sanders, Baron & Moore, 1978) and make greater use of contextual cues when forming an impression of a target (Thomas et al, 2002).…”
Section: Farm Modelmentioning
confidence: 63%
“…As such, it is possible that the presence of others, instead of engaging individuals in a task, makes them more sensitive to the context. In line with this hypothesis, Fonseca and Garcia-Marques (2010) have demonstrated that, compared to an alone situation, the presence of others increases the amount of contextrelated free-associations (experiment 1) and the accuracy for estimation judgments that require the integration of contextual information (experiment 3). This context-sensitivity hypothesis can also be found in social facilitation evidence that shows that accompanied individuals have better recall for contextual aspects of the task-situation, (Sanders, Baron & Moore, 1978) and make greater use of contextual cues when forming an impression of a target (Thomas et al, 2002).…”
Section: Farm Modelmentioning
confidence: 63%
“…Being so, presence of others may, in some way, help us to attend to those goals. One possible way can be the fact that it promotes more access to context features and so access to detailed features of a face (Fonseca & Garcia-Marques, 2013) which help to better detect differences between faces.…”
Section: Discussionmentioning
confidence: 99%
“…in the Stroop task; Huguet et al, 1999) or impairment. In addition to evidence suggesting that SP increases reliance on well-learned responses and activity of executive control functions, there is also evidence that SP increases the "spreading out" of one's thoughts (Allport, 1920) increasing individuals' sensitivity to contextual influences (Fonseca & Garcia-Marques, 2013).…”
Section: Social Presence Modulation Of Face Holistic Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…167–168). Recently, Fonseca and Garcia-Marques [ 2 ], using a task that measures sensitivity to contextual information–framed-line test [ 3 ], showed further evidence of this effect. The authors asked participants to reproduce a previously observed line identically (absolute task) or proportionally (relative task) in a new surrounding frame.…”
Section: Introductionmentioning
confidence: 99%